Industrial hemp seed: from the field to value-added food ingredients - Rachel A. Burton; Mike Andres; Martin Cole; James M. Cowley; Mary Ann Augustin (BMC, 2022)
Abstract Industrial hemp, with low levels of the intoxicating cannabinoid tetrahydrocannabinol (THC), is grown for fibre and seeds. The industrial hemp industry is poised for expansion. The legalisation of industrial hemp as an agricultural commodity and the inclusion of hemp seed in foods is helping to drive the expansion of the hemp food ingredients industry. This paper discusses the opportunity to build an industrial hemp industry, with a focus on the prospects of hemp seed and its components in food applications. The market opportunities for industrial hemp products are examined. Various aspects of the science that underpins the development of an industrial hemp industry through the food supply chain are presented. This includes a discussion on the agronomy, on-farm and post-harvest considerations and the various types of food ingredients that can be made from hemp seed. The characteristics of hemp seed meal, hemp seed protein and hemp seed oil are reviewed. Different processes for production of value-added ingredients from hemp seed, hemp seed oil and hemp seed protein, are examined. The applicability of hemp seed ingredients in food applications is reviewed. The design of hemp seed ingredients that are fit-for-purpose for target food applications, through the selection of varieties and processing methods for production of various hemp seed ingredients, needs to consider market-led opportunities. This will require an integrated through chain approach, combined with the development of on-farm and post-farm strategies, to ensure that the hemp seed ingredients and foods containing hemp seed are acceptable to the consumer.